The Spirit of Parakang in The Bugis Myth of Indonesia: an Islamic Educational Perspective - Yeyeng, Andi Tenri; Tajuddin, Muhammad Saleh; Saleh, Eliza Farahdiba (Jurnal Adabiyah, 2024)
This research explores the concept of parakang in the Bugis myth of Indonesia, addressing three main questions: How does the phenomenon of parakang emerge as part of the mystical beliefs in the Bugis community? What impact does parakang have on the Bugis community? What role does Islamic education play in mitigating the effects of parakang-related violence? These questions are the focus of the discussion. The research aims to scientifically examine the Bugis people's myth surrounding the existence of parakang, a creature believed to be highly disruptive to the community. To analyze its emergence and societal impact, the research applies Durkheim's and Popper's perspectives on metaphysical realism. Additionally, James A. Banks' Theory of Multicultural Education is utilized to explore how cultural diversity in education can address these challenges. This research employs a qualitative method with a phenomenological approach. Primary data were gathered through observations and interviews, while secondary data were sourced from texts, e-books, journals, video documentaries, parakang-related films, and the internet.The findings are as follows: Several factors contribute to the emergence of parakang, including pesugihan (seeking wealth through mystical means), supernatural orders, heredity, the transmission of the sakratul maut (the agony of death), and frequent visits to shamans. Parakang victims often experience severe illness and, in some cases, death. Islamic education provides a critical perspective, highlighting that the concept of parakang contradicts Islamic teachings. As a result, it is essential to equip the younger Muslim generation with a robust Islamic education to prevent them from being influenced by parakang-related beliefs.This research explores the concept of parakang in the Bugis myth of Indonesia, addressing three main questions: How does the phenomenon of parakang emerge as part of the mystical beliefs in the Bugis community? What impact does parakang have on the Bugis community? What role does Islamic education play in mitigating the effects of parakang-related violence? These questions are the focus of the discussion. The research aims to scientifically examine the Bugis people's myth surrounding the existence of parakang, a creature believed to be highly disruptive to the community. To analyze its emergence and societal impact, the research applies Durkheim's and Popper's perspectives on metaphysical realism. Additionally, James A. Banks' Theory of Multicultural Education is utilized to explore how cultural diversity in education can address these challenges. This research employs a qualitative method with a phenomenological approach. Primary data were gathered through observations and interviews, while secondary data were sourced from texts, e-books, journals, video documentaries, parakang-related films, and the internet. The findings are as follows: Several factors contribute to the emergence of parakang, including pesugihan (seeking wealth through mystical means), supernatural orders, heredity, the transmission of the sakratul maut (the agony of death), and frequent visits to shamans. Parakang victims often experience severe illness and, in some cases, death. Islamic education provides a critical perspective, highlighting that the concept of parakang contradicts Islamic teachings. As a result, it is essential to equip the younger Muslim generation with a robust Islamic education to prevent them from being influenced by parakang-related beliefs. الملخص يتناول هذا البحث الباراكانغ في أساطير شعب البوجيس بإندونيسيا. ويوضح البحث أن ظاهرة الباراكانغ ظهرت كجزء من المعتقدات الصوفية لمجتمع البوجيس، وتأثير الباراكانغ على مجتمع البوجيس، ودور التربية الإسلامية في التقليل من تأثير عنف الباراكانغ. سيتم مناقشة هذه المشكلة بشكل علمي لكشف أسطورة مجتمع البوجيس حول وجود الباراكانغ، والذي يشكل وجوده إزعاجًا كبيرًا للمجتمع. لتحليل ظهور الباراكانغ وتأثيره الاجتماعي، يستخدم هذا البحث نظرية الواقعية الميتافيزيقية لدوركهايم وبوبر. بالإضافة إلى ذلك، تُستخدم نظرية التعليم متعدد الثقافات لجيمس أ. بانكس لاستكشاف التنوع الثقافي في التعليم كوسيلة للتغلب على هذه التحديات. يستخدم هذا البحث البحث النوعي مع النهج الظاهري. تم الحصول على البيانات الأولية من خلال الملاحظة والمقابلات. تم الحصول على البيانات الثانوية من نصوص الكتب الإلكترونية والمجلات وأفلام الفيديو الوثائقية وأفلام باراكانغ والإنترنت. وكانت النتائج التي تم التوصل إليها أن هناك عدة أسباب لظهور الباراكانغ، بما في ذلك: بيسوجيهان، والأوامر السحرية، والعوامل الوراثية، وانتقال مقدس الموت، والزيارات المتكررة للشامان. يمكن أن يتسبب ضحايا باراكانغ في مرض خطير وحتى الموت. عند مراجعة التعليم الإسلامي، فإن الباراكانغ يتعارض مع التعاليم الإسلامية. ولذلك، يجب تزويد جيل الشباب من المسلمين بتربية إسلامية جيدة حتى لا يصبحوا فريسة للباراكانغ. AbstrakPenelitian ini membahas tentang parakang dalam mitos masyarakat Bugis, Indonesia. Penelitian menjelaskan fenomena parakang muncul sebagai bagian dari kepercayaan mistik masyarakat Bugis, dampak parakang terhadap masyarakat Bugis dan peran pendidikan Islam dalam meminimalisasi dampak keganasan parakang. Permasalahan tersebut akan dibahas secara ilmiah untuk mengungkap mitos masyarakat Bugis terkait eksistensi parakang yang keberadaannya cukup meresahkan masyarakat. Untuk menganalisis kemunculan dan dampak sosial parakang, penelitian ini menggunakan teori Durkheim dan Popper tentang realisme metafisik. Selain itu, teori pendidikan multikultural James A. Banks digunakan untuk mengeksplorasi keragaman budaya dalam pendidikan sebagai cara untuk mengatasi tantangan tersebut. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan fenomenologis. Data primer diperoleh melalui observasi dan wawancara. Data sekunder diperoleh dari teks e-book, jurnal, video dokumenter, film parakang, dan internet. Hasil yang ditemukan adalah adanya beberapa penyebab munculnya parakang, di antaranya: pesugihan, perintah kesaktian, faktor keturunan, penularan sakratul kematian, dan seringnya kunjungan ke dukun. Korban parakang dapat menyebabkan penyakit parah bahkan kematian. Dalam tinjauan pendidikan Islam, parakang bertentangan dengan ajaran Islam. Oleh karena itu, generasi muda Islam harus dibekali dengan pendidikan Islam yang baik agar tidak menjadi mangsa parakang.